Dynamics of vapour bubbles induced during the boiling of superfluid helium under microgravity conditions. (May 2019) - Grunt, Krzysztof; Lewkowicz, Marek; Pietrowicz, Sławomir; Takada, Suguru; Kimura, Nobuhiro; Murakami, Masahide
Highlights: A model for a spherical vapour bubble submerged in superfluid helium was developed. The model was validated using empirical data obtained under microgravity conditions. The physics of the Knudsen layer have a strong impact on the dynamics of the system. The results indicate a rather high value of the associated accommodation coefficient. Abstract: The presented research aims to establish a theoretical framework for the analysis of the transient behaviour of vapour bubbles resulting from superfluid helium boiling under the conditions of microgravity. As long as the volume of a bubble is small in comparison with the volume of a container, the dynamics of the surrounding liquid and interfacial momentum transfer seem to be the dominant factors determining the pace of bubble growth. This notion leads to a relatively clear mathematical description of the system. A pair of 1st order ODEs was formulated on the basis of the mass and momentum conservation principles applied to the liquid phase as well as the assumption of the perfect spherical symmetry of a bubble. In order to obtain the empirical data necessary for the validation of the model, an experimental campaign has been conducted at the ZARM Drop Tower. A dedicated cryostat equipped with optical windows has been utilised in order to achieve superfluidity. The boiling was procured using a 1.88 mm long segment of manganin wire, measuring 50  μ m in diameter. The vapour-liquid interface was tracked using a high-speed camera equipped with two separate heads positioned along two perpendicular axes. A reasonable agreement between the model predictions and the empirical data has been observed, indicating the suitability of the framework for the analysis of superfluid helium boiling.